2017
DOI: 10.1016/j.molliq.2016.09.090
|View full text |Cite|
|
Sign up to set email alerts
|

Random-phase-approximation theory for sequence-dependent, biologically functional liquid-liquid phase separation of intrinsically disordered proteins

Abstract: Intrinsically disordered proteins (IDPs) are typically low in nonpolar/hydrophobic but relatively high in polar, charged, and aromatic amino acid compositions. Some IDPs undergo liquid-liquid phase separation in the aqueous milieu of the living cell. The resulting phase with enhanced IDP concentration can function as a major component of membraneless organelles that, by creating their own IDP-rich microenvironments, stimulate critical biological functions. IDP phase behaviors are governed by their amino acid s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
222
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(229 citation statements)
references
References 117 publications
(281 reference statements)
6
222
1
Order By: Relevance
“…and G k G k 12 21 = ( )ˆ( ). As in our previous studies [61,62], we consider a simple formulation in which all IDPs are modeled as Gaussian chains without excluded volume within the RPA formalism [66]. In this approximation, there is no correlation between the positions of different chains; hence G k G k 0 12 21 = = ( )ˆ( ) and One phase is concentrated in seq2 but dilute in seq1 (top), the other phase is concentrated in seq1 but dilute in seq2 (bottom).…”
Section: Free Energy As a Function Of Two Idp Volume Fractionssupporting
confidence: 59%
See 2 more Smart Citations
“…and G k G k 12 21 = ( )ˆ( ). As in our previous studies [61,62], we consider a simple formulation in which all IDPs are modeled as Gaussian chains without excluded volume within the RPA formalism [66]. In this approximation, there is no correlation between the positions of different chains; hence G k G k 0 12 21 = = ( )ˆ( ) and One phase is concentrated in seq2 but dilute in seq1 (top), the other phase is concentrated in seq1 but dilute in seq2 (bottom).…”
Section: Free Energy As a Function Of Two Idp Volume Fractionssupporting
confidence: 59%
“…being the i j , element of the bare two-body correlation matrix G k of all possible sequence-sequence correlations [62],…”
Section: Free Energy As a Function Of Two Idp Volume Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobs and Frenkel used Monte Carlo simulations to study 37 multiple-component phase separation and found that the phase boundary is very 38 sensitive to intermolecular interactions, but less dependent on the number of 39 components in the system [36]. Lin and Chan applied the random phase approximation 40 to treat electrostatic interactions [37] and Flory Huggins theory for mixing entropy and 41 other interactions. They were able to capture the sequence specificity of charged amino 42 acids and found that the dependence of the phase boundary of the IDP Ddx4 on salt 43 concentration can be explained by considering only electrostatic screening in their 44 model [38].…”
mentioning
confidence: 99%
“…To understand the mechanism of such dependence, we apply Flory-Huggins 430 theory [79,80], which has previously been used to understand IDP phase 431 separation [9,37,38], to fit the phase transition properties obtained by molecular 432 dynamics simulations when varying the chain length N . If we assume that each solvent 433 molecule occupies one lattice position, then the the critical temperature 434 T c ∝ N/( √ N + 1) 2 and the critical concentration ρ c ∝ 1/( √ N + 1).…”
mentioning
confidence: 99%